Assessment of Influencer Marketing in the Nigerian Public Relations Industry - Omolara Oluwabusayo Akin-Odukoya; Joshua Kayode Okunade; Sunday Ogbonna; Funmi Falobi (Britain International of Humanities and Social Sciences (BIoHS) Journal, 2025)
This study deals with assessment of influencer marketing in the Nigerian public relations industry. This paper employed The Media Consumption Theory and Uses and Gratifications Theory (UGT). The theories of media consumption focus on the method and reasons media contents are engaged, such as the selection, interpretation, and response to media content, and how consumers are affected by media in the sense that social media platforms have revolutionized the interaction and sharing of information, facilitating global connectivity and nurturing communities. Nigeria's consumer environment is diverse. Two prominent trends are the middle class and increasing urbanisation. As more Nigerians move into cities and their incomes rise, consumer behaviour is moving towards modern shop formats. This is a reflection of consumers' desire for better products in emerging markets. Modern commerce channels such as supermarkets and shopping malls are growing in popularity. The changing needs of urban consumers for convenience, variety of products, and a more structured shopping experience are reflected in this growth. It can be conclude that Influencer marketing has become a powerful and indispensable tool in the Nigerian public relations industry, transforming the way brands engage with their audiences. Its ability to foster authenticity, drive consumer trust, and enhance brand visibility has positioned it as a preferred strategy over traditional advertising methods. While challenges such as fake engagement metrics, regulatory gaps, and audience saturation persist, a data-driven and strategic approach can mitigate these issues, ensuring effective campaigns.